Development of Digital Flipbook-Based Learning Media on Norms in Everyday Life in Class IV SD 89 Palembang - Arni, Yusni; Feliz, Lista Anisa; Sari, Dira Permata; Jesika, Intan (CV. PUSDIKRA MITRA JAYA, 2025)
This research aims to develop learning media in the form of digital flipbooks to improve the understanding of grade IV students at SD Negeri 98 Palembang about the application of Pancasila values. The method used in this research is research and development (R&D) with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. This digital flipbook media is designed to present material about Pancasila in an interactive and interesting way. The results showed an increase in students' understanding of Pancasila values after using this media, which can be seen from the better test results in the post-test compared to the pre-test. In addition, student engagement during the learning process also increased, and feedback from students and teachers showed that this media has high visual appeal and easy to understand material. Based on the evaluation results, it can be concluded that this digital flipbook-based learning media is effective in improving understanding of Pancasila values for fourth grade elementary school students.